Factors Affecting the Innaccuracy of Outpatient Disease Diagnosis Coding in General Surgery and Neurosurgery Polyclinics, Hospital X, Badung Regency - Ni Luh Eka Septiari Suriawan; Bambang Hadi Kartiko; Budhimuljono Adhiwirawan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2017)
The purpose of this research was to investigate the correlation of coder’s comprehension, audit implementation, medical record the completeness, SOP implementation, as well as facilities and infrastructure completeness with the inaccuracy of outpatient diagnosis coding in General Surgery and Neurosurgery Polyclinics, Hospital X, Badung Regency. This research was quantitative analytic research with cross-sectional study design. A total of 8 coders were sampled and as many as 200 medical records were selected for the determination of coding inaccuracy. The results showed that most medical records are inaccurately coded. The bivariate test using spearman's who indicated that there was a correlation between the coder’s comprehension (sig. = 0.000), audit implementation (sig. = 0.003), medical record completeness (sig. = 0.000), SOP implementation (sig. = 0.004), as well as facilities and infrastructure completeness (sig. = 0.000) with the inaccuracy of outpatient disease diagnosis coding.